21
Аноним
Математика
15 января 21:44

1.Упростите выражение: а)(3а-1)(2а+7); б)(5к+2)(3-2к); в)а(а+4)-(а-2)(а+6); г)(1-3с)(9+3с+1).

Ответ или решение1

а )( 3 а - 1 ) ( 2 а + 7 ) = 6 * а в квадрате + 21 * а - 2 * а - 7 = 6 * а в квадрате + 19 * а - 7 б ) ( 5 к + 2 ) ( 3 - 2 к ) = 15 * к - 10 * к в квадрате + 6 - 4 * к = - 10 * к в квадрате + 11 * к + 6 ; в) а ( а + 4 ) - ( а - 2 ) ( а + 6 ) = а в квадрате + 4 * а - ( а в квадрате + 6 * а - 2 * а - 12 ) = а в квадрате + 4 * а - а в квадрате - 4 * а + 12 = 4 * а - 4 * а + 12 = 12; г ) ( 1 - 3 * с ) ( 9 + 3 с + 1 ) = 9 + 3 * с + 1 - 27 * с - 9 * с в квадрате - 3 * с = 10 - 27 * с - 9 * с в квадрате
0 / 10000
ВходРегистрация

Вход

или

Регистрация